Medication Needs Vary for Terminally Ill Vietnam Era Veterans With and Without a Diagnosis of PTSD. (August 2016) - Kelley-Cook, Esther; Nguyen, George; Lee, Shuko; Edwards, Tressia M.; Sanchez-Reilly, Sandra
This retrospective pilot study aims to evaluate the clinical impact of palliative care in the treatment of terminally ill Vietnam Veterans with a history of posttraumatic stress disorder (PTSD) versus those without PTSD, as it pertains to medications for symptom control at the end of life (EOL). Active prescriptions for benzodiazepines, hypnotics, antidepressants, and antipsychotic medications at the EOL were recorded. During EOL care, 28 (72%) participants with PTSD used these medications versus 55 (40%) of the non-PTSD participants ( P = .0005). There was significant correlation between a lifetime diagnosis of PTSD with antidepressant use ( P = .0002) and hypnotics ( P = .0085) during EOL care but not with benzodiazepines or antipsychotics. The higher utilization of certain medication classes among participants with PTSD may indicate that PTSD treatment should continue at the EOL to improve care.